The text of the Targum of Job : an introduction and critical edition - Stec, David M. (Arbeiten zur Geschichte des antiken Judentums und des Urchristentums, 1994)
The centrepiece of this book is a critical edition of the Targum of Job which notes all variants from a total of 14 manuscripts and 2 printed editions. In the introductory section the first two chapters give a description of the principal printed editions and the manuscripts. A chapter on \'The Stemma\' considers how the various strands of textual tradition relate to each other. There is also a chapter on \'Multiple Translation\', a phenomenon particularly associated with the Targum of Job whereby more than one translation is often given to whole verses or to individual words and phrases. A final chapter describes in detail the methods underlying the critical edition. This book will provide a useful tool for those working on the textual criticism of the Old Testament and for those interested in the history of Jewish biblical exegesis.